East central European foreign policy identity in perspective : back to Europe and the EU's Neighbourhood - Tulmets, Elsa; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
How have countries in the EU that were previously under Communist rule influenced the creation of a European policy towards other Post-Soviet nations? This study explores countries including the Czech Republic and Poland and shows how they have helped develop a coherent policy based reconciling political and historical foreign policy identities.
Keywords: Political science; Political theory; Democracy; European Union; Russia -- Politics and government; International relations; Political Science and International Relations; Russian and Post-Soviet Politics; International Relations; European Union Politics; Democracy; Political Science; Political Theory